NK cells and pre-eclampsia. - Sargent, I; Borzychowski, A; Redman, C (2007)
The immunological interaction between the mother and fetus has classically been thought of as one between paternal antigen and maternal T cells. However, the MHC antigen expression on human trophoblast and the immune cell populations present in the decidua suggest that this interaction primarily involves decidual NK cells rather than T cells, and this is supported by new functional studies. It is becoming apparent also that the maternal systemic immune response in pregnancy (Th1/Th2 shift) primarily involves NK cells. Aberrant NK cell activation both locally in the decidua and systemically in the maternal blood may be the cause of pre-eclampsia.